Sleep in children with Smith–Magenis syndrome: a case–control actigraphy study. Issue 4 (20th October 2019) - Trickett, Jayne; Oliver, Chris; Heald, Mary; Denyer, Hayley; Surtees, Andrew; Clarkson, Emma; Gringras, Paul; Richards, Caroline
Abstract: Study Objectives: The objectives of the study were (1) to compare both actigraphy and questionnaire-assessed sleep quality and timing in children with Smith–Magenis syndrome (SMS) to a chronologically age-matched typically developing (TD) group and (2) to explore associations between age, nocturnal and diurnal sleep quality, and daytime behavior. Methods: Seven nights of actigraphy data were collected from 20 children with SMS (mean age 8.70; SD 2.70) and 20 TD children. Daily parent/teacher ratings of behavior and sleepiness were obtained. Mixed linear modeling was used to explore associations between total sleep time and daytime naps and behavior. Results: Sleep in children with SMS was characterized by shorter total sleep time (TST), extended night waking, shorter sleep onset, more daytime naps, and earlier morning waking compared to the TD group. Considerable inter-daily and inter-individual variability in sleep quality was found in the SMS group, so caution in generalizing results is required. An expected inverse association between age and TST was found in the TD group, but no significant association was found for the SMS group. No between-group differences in sleep hygiene practices were identified. A bidirectional negative association between TST and nap duration was found for the SMS group. In the SMS group, increased afternoon sleepiness was associated with increased irritability ( p = .007) and overactivity ( p = .005). Conclusion: These findings evidence poor sleep quality in SMS and the need to implement evidence-based interventions in this population.